Morphological and Sedimentation Characteristics of Air Rami Estuary: Implications for Shape Changes: Karakteristik Morfologi dan Sedimentasi Muara Air Rami: Implikasi terhadap Perubahan Bentuk - Rani Fuad Cahyani; Supiyati Supiyati; Suwarsono Suwarsono (Academia Open, 2023)
Focusing on the swiftly transforming estuary of the Air Rami River in Mukomuko District, this study investigates the intricate interplay between morphological and sedimentation attributes and their influence on estuarine morphology. The research seeks to elucidate the effects of these characteristics on shaping the Air Rami Estuary. Employing direct field measurements and laboratory analyses, data encompassing river flow velocity, discharge parameters, sediment influx, samples, and estuary imagery from USGS were collected in March 2023. Notably, the highest and lowest river flow discharges were 29.32 m3/s and 16.42 m3/s, respectively, while sedimentation rates ranged from 0.037 kg/s to 0.042 kg/s, and sediment influx varied between 0.18 m3/s and 1.26 m3/s. The findings underscore the pivotal role of morphological and sedimentation dynamics in shaping the estuary's form, yielding valuable insights into coastal morphological evolution and management strategies. Highlight: Estuary Transformation: This study delves into the rapidly evolving Air Rami River estuary, unraveling the intricate interaction between Morphological Attributes and Sedimentation Dynamics that shape its morphology. Comprehensive Analysis: Employing direct measurements and laboratory analyses, the research captures a range of River Flow Discharges, Sedimentation Rates, and Sediment Influx, shedding light on the multifaceted processes at play. Implications for Management: The findings highlight the fundamental role of morphological and sedimentation dynamics, offering valuable insights for Coastal Management Strategies and informed decision-making in coastal environments. Keyword: Air Rami Estuary, Morphological Attributes, Sedimentation Dynamics, Estuarine Morphology, Coastal Management